1999
DOI: 10.1136/gut.45.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to human gastric epithelial cells and heat shock protein 60 in Helicobacter pylori positive mucosa associated lymphoid tissue lymphoma

Abstract: Background-Development of gastric mucosa associated lymphoid tissue (MALT) lymphoma is thought to be closely associated with host immune reactions to Helicobacter pylori. Aim-To investigate humoral immune responses in patients with MALT lymphoma to antigens shared by H pylori and human gastric epithelial cells. Methods-Sera were obtained from H pylori positive patients with MALT lymphoma (n = 11) or other gastroduodenal diseases (peptic ulcer, n = 40; nonulcer dyspepsia, n = 20) and from H pylori negative heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…Bacterial Hsps may play an important role in inflammation (71), and human Hsp60 and H. pylori HspB have antigenic similarities (31). An Hsp60 epitope is detected on the surface of both human gastric cancer cells and human gastric biopsy specimens, and the intensity of cell surface Hsp60 correlated significantly with adhesion of H. pylori to human gastric cancer cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial Hsps may play an important role in inflammation (71), and human Hsp60 and H. pylori HspB have antigenic similarities (31). An Hsp60 epitope is detected on the surface of both human gastric cancer cells and human gastric biopsy specimens, and the intensity of cell surface Hsp60 correlated significantly with adhesion of H. pylori to human gastric cancer cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, H. pylori-derived HSP60 (Hp-HSP60) is an important antigen that is abundantly expressed under various environmental stressors 113) . Hp-HSP60 has been found to appear on antigen-presenting cells in the germinal center in the gastric lymphoid tissues of patients infected with H. pylori 114) , and antibodies cross-reactive to both endogenous HSP60 and Hp-HSP60 have been found in the sera of H. pyloriinfected patients 115,116) . Notably, IgG antibodies against a particular amino acid sequence of Hp-HSP60 are able to recognize full-sequenced human HSP60, indicating that immune responses against HSP60 of pathogenic origin are misdirected to a human counterpart 117) .…”
Section: H Pylori and Oxidative Stressmentioning
confidence: 99%
“…Our previous studies have shown that the 60-kDa hsp (hsp60) is expressed in the follicular dendritic cells of the gastric mucosa in patients with gastric MALT lymphoma (15) and that antibodies to human hsp60 can be detected in MALT lymphoma patients (14). These results indicate that hsp60 may be associated with the host immune reaction in H. pylori infection, specifically, the pathogensis of gastric MALT lymphoma.…”
mentioning
confidence: 82%
“…Diagnosis of the other diseases was determined according to the symptoms and by endoscopy. Infection with H. pylori was confirmed by culture, the rapid urease test, and histology of gastric biopsy specimens and by the presence of serum antibodies to H. pylori as detected by enzyme-linked immunosorbent assay (ELISA) (14). H. pylori was detected in the gastric mucosae of all patients whose sera were positive for anti-H. pylori antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation